Essential oil yield and composition of rose-scented geranium (Pelargonium sp.) as influenced by harvesting frequency and plant shoot age - Soundy, Puffy (University of Pretoria, 2013)
Dissertation (MSc(Agric) (Agronomy))--University of Pretoria, 2007.